Perspective Supervision in Islam - Iwan Setiawan; Agus Gunawan; Enung Nugraha (International Journal of Advanced Technology and Social Sciences, 2023)
In the Islamic context, educational supervision has high relevance, as education is considered one of the important aspects in the development of spiritually and academically balanced individuals. This article discusses educational supervision from an Islamic perspective and explains the principles, objectives, and methods of supervision that are in accordance with Islamic values. Theoretical Studies: This article refers to various sources of theory in Islam that are relevant to educational supervision. Some of the concepts that are in focus are "tarbiyah" (coaching), "science" (science), and "amanah" (amanah). Methodology: This study uses an analytical descriptive approach by analyzing Islamic literature and sources relevant to educational supervision. The data were analyzed qualitatively to understand the principles of educational supervision in Islam. The results of this study identify several principles of educational supervision in Islam, including: Respect and Relationship Building: Supervision in Islam is based on the values of mutual respect and building a good relationship between the supervisor and the supervised. Coaching and Development: The main objective of supervision in Islam is the formation and development of individuals to reach their true potential, both academically and spiritually. Justice and Fair Leadership: Supervision of education in Islam should be fair and just-based, with supervisors acting as just and responsible leaders. Supervision of education in Islam has a strong foundation of principles that include Islamic values such as justice, guidance, and trust. Understanding and applying these principles in the practice of educational supervision can help create an educational environment that conforms to Islamic values and contributes to the development of spiritually and academically balanced individuals.